2020
DOI: 10.1186/s12889-019-8077-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trauma-informed care on hair cortisol concentration in youth welfare staff and client physical aggression towards staff: results of a longitudinal study

Abstract: Background: Professional caregivers working in child and youth welfare institutions are frequently faced with the complex mental health issues, emotional needs and challenging coping strategies of clients with cumulated traumatic experiences, leaving them prone to developing high levels of stress, burn-out and compassion fatigue. Trauma-informed care (TIC) is a milieu-therapeutic approach that aims to promote the self-efficacy and self-care of youth welfare staff by guiding them to a better understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 67 publications
(101 reference statements)
0
16
0
Order By: Relevance
“…Guiding principles of trauma informed care include: safety, trustworthiness and transparency, peer support, collaboration and mutuality, empowerment and choice, and cultural, historical and gender issues (see also the infographic on the website of the Office of Public Health Preparedness and Response [OPHPR] of the Center for Disease and Control Prevention [CDC]: https://www.cdc.gov/cpr/infographics/6_principles_trauma_info.htm ). 2 This trauma informed approach has also been examined in the more specific context of the juvenile justice system [ 70 , 71 ]. Although the combination of evidence-based trauma-therapeutic interventions in combination with trauma informed care concepts is highly promising for the treatment of, for example juvenile offenders (but also adolescents in the child welfare system), more research is warranted to examine its impact on offending behavior/recidivism as well as other adolescent/adult functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Guiding principles of trauma informed care include: safety, trustworthiness and transparency, peer support, collaboration and mutuality, empowerment and choice, and cultural, historical and gender issues (see also the infographic on the website of the Office of Public Health Preparedness and Response [OPHPR] of the Center for Disease and Control Prevention [CDC]: https://www.cdc.gov/cpr/infographics/6_principles_trauma_info.htm ). 2 This trauma informed approach has also been examined in the more specific context of the juvenile justice system [ 70 , 71 ]. Although the combination of evidence-based trauma-therapeutic interventions in combination with trauma informed care concepts is highly promising for the treatment of, for example juvenile offenders (but also adolescents in the child welfare system), more research is warranted to examine its impact on offending behavior/recidivism as well as other adolescent/adult functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of validated treatment programs for female JSOs, it could be argued that (parts of) male JSOs treatment approaches could be applied for the treatment of female JSOs, although adjusted to suit a female perspective (e.g., by including examples of female JSOs in treatment manuals). In addition, trauma-informed care, which is also receiving increasing attention within the forensic field (Branson et al, 2017;Schmid et al, 2020), could not only benefit female, but also male offenders. Nevertheless, there is a risk for a "one size fits all" approach, and despite the many similarities, the diversity of the group, however, should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, two recent systematic reviews concluded that self-care still takes a back seat in social work, and little is known about the efficacy of specific self-care practices ( 93 , 94 ). Trauma-informed care (TIC) concepts that also focus on implementing resilience practices for caregivers might be a promising approach for reducing the emotional burden of employees and institutions and were shown to reduce hair cortisol levels of caregivers that were trained in TIC ( 95 ). However, more intervention research implementing psychophysiological assessments of stress that replicate our findings in prospective, longitudinal studies and the integration of such findings into educational programs is needed for improving resilience and maintaining empowered and healthy caregivers.…”
Section: Discussionmentioning
confidence: 99%